Features of Unmanned Aircraft Detection Using Precision Approach Radar - E. A. Rubtsov; A. V. Fedorov; N. V. Povarenkin; M. Al-Rubaye (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The increasing number of incidents involving unmanned aerial vehicles (UAVs) makes their detection in the aerodrome area an important task, which can be solved by specialized surveillance means. However, the application of such means requires certification procedures confirming the effectiveness and safety of their use. Therefore, in the short term, it seems reasonable to use standard technologies. In the approach sector, this task can be solved by precision approach radar systems. The small radar cross-section (RCS) of UAVs leads to a decrease in the maximum range and the appearance of blind spots, within which the vehicle cannot be detected.Aim. Analysis of the possibility of detecting UAVs using a precision approach radar, assessing the maximum detection range, blind spots and developing recommendations for their reduction.Materials and methods. An analytical method was used for determining the maximum detection range for a precision approach radar, taking into account UAV characteristics. A method for estimating the detection range of a low-flying target, taking into account the influence of the underlying surface, was also used.Results. Using the example of the precision approach radar RP-5G, the maximum detection ranges were determined, which amounted to 380, 2730, 4480 and 14350 m for UAVs with an RCS of 0.01, 0.05, 0.1 and 0.5 m2, respectively. The length of the blind spots of the RP-5G was 4620, 2270, 1019 m for UAVs with an RCS of 0.01, 0.05, 0.1 m2, respectively. Under the vehicle RCS of 0.5 m2 and greater, no blind spots are observed.Conclusion. Analytical expressions for calculating the maximum detection range and blind spots were obtained. The results can be used when assessing specific features of UAV observation in the aerodrome area (landing sector). Standard precision approach radar systems can be used when surveying UAVs with an RCS greater than 0.5 m2. For UAVs with an RCS of 0.1...0.5 m2, modernized precision approach radar systems with an increased probing pulse energy should be implemented.